O biegunie – językoznawczo (rozważania w kontekście tytułu powieści Olgi Tokarczuk Bieguni) - Maciołek, Marcin (Postscriptum Polonistyczne, 2020)
The paper contains a historical linguistic analysis of the noun biegun. It was prompted by the inflectional form of the plural nominative bieguni, the title of one of Olga Tokarczuk’s novels, a form unusual from the point of view of the contemporary Polish grammatical system. Tokarczuk used the form ending in -i, typical of masculine personal nouns, while the word biegun is commonly known to be used nowadays only in meanings that do not refer to people. This is why the paper attempts to gain insight into the semantics of the lexeme biegun in the history of the Polish language. The research carried out made it possible to determine that the examined unit used to function in many personal meanings in the past, meanings that would eventually become obsolete with the gradual lexicalization of the word biegun and in relation the appearance of its derivational synonyms in the Polish language. Tokarczuk thus revived some of the old meanings of the word biegun referring to people, and at the same time brought out new, metaphorical meanings embedded in it in potentia – thus delexicalizing the examined unit.